The mixed bag of Mimiocurus bark beetles (Coleoptera, Curculionidae): 18 species redistributed on 10 genera in 7 tribes! - Jordal, Bjarte H. (Zootaxa, 2026)
The genus Mimiocurus Schedl, 1957 has a complicated taxonomic history and is revised. Previous classifications were critically flawed due to the superficial examination of few morphological characters. Dissections of internal morphological characters, including proventriculus, mouthparts, male genitalia, and flight wings, provided highly informative characters that resulted in the transfer of 11 species to other genera in six different tribes. This is an extraordinarily high number of taxonomic changes involving many completely unrelated lineages and therefore illustrates the importance of using a broad array of morphological characters in the classification of bark beetle species. New taxonomic changes include Mimiocurus to Ipini, Dendrotomicus Jordal, gen. nov. to accommodate Dendrotomicus kikusuae Schedl, 1957 comb. nov. and Dendrotomicus rugicollis Schedl, 1957 comb. nov. (=Mimiophthorus kikusuae spp. occidentalis syn. nov.), and Pityophthorus oleanderi (Schedl, 1961) comb. nov. all remaining in Corthylini, Cyrtogenius orientalis (Schedl, 1972) comb. nov., and Cyrtogenius rosseli (Schedl, 1973) comb. nov. to Dryocoetini, Acanthotomicus superciliosus, Jordal nom. nov. (for A. congonus Schedl, 1952 comb. nov., preoccupied) and Acanthotomicus umbratus (Schedl, 1972) comb. nov. to Ipini, Afromicracis ruwenzoriensis (Schedl, 1963) comb. nov., and Micracidendron montanum (Schedl, 1957) comb. res. to Micracidini, Polygraphus militaris (Eggers, 1919) (=Mimiophthorus uniseriatus Schedl, 1979 syn. nov., to Polygraphini), and Macrocryphalus beesoni (Wood, 1989) comb. nov., to Trypophloeini. Two new species are described, Mimiocurus mucronatus Jordal sp. nov. and Micracidendron atrum Jordal sp. nov. A revised key to the four species in Mimiocurus is provided together with a modified key to place Micracidendron in Micracidini.